Comments of the Max Planck Institute for Intellectual Property, Competition and Tax Law on the white paper by the directorate-general for competition of April 2008 on damages actions for breach of the EC antitrust rules - Drexl, J; Gallego, B; Enchelmaier, S; Mackenrodt, M; Podszun, K (2008)
The Max Planck Institute for Intellectual Property, Competition and Tax Law is a research institute within the Max Planck Society for the Advancement of Arts and Science. The Max Planck Institute undertakes research on fundamental questions of law in these areas. The Institute regularly advises governmental bodies and other organizations at the national and international level. It has an international approach and places emphasis on the comparative analysis of law as well as economic and technological aspects of legal developments.